The Stewarding Service as a Security Mechanism at Public Gatherings: A Critical Assessment in the Context of the Public Gatherings Act (ZJZ) and the Private Security Act (ZZaSV-1) - Dvojmoč, Miha (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
The stewarding service represents an important security mechanism for maintaining order, directing participants, and preventing incidents at public gatherings. According to the Public Gatherings Act (»Zakon o javnih zbiranjih (ZJZ-UPB5)«, 2011), the organiser is obliged to provide an adequate number of qualified stewards who meet specific conditions, while the Private Security Act (»Zakon o zasebnem varovanju (ZZaSV-1)«, 2011) sets out the requirements and competences of security guards, who often perform duties at the same events. Although stewards have a very similar role to security guards, they are not employed under the provisions of the Private Security Act. Significant differences exist between these two services regarding rights, responsibilities and working conditions, leading to considerable legal and operational ambiguities. Notable shortcomings are also present in the statutory regulation of supervision over stewarding services. Therefore, a clearer delineation of tasks and competences, and harmonised legal regulation of both areas, would be advisable. This would ensure more effective and safer implementation of public gatherings for all participants.